2019
DOI: 10.3390/cells8111418
|View full text |Cite
|
Sign up to set email alerts
|

Increased Adipose Tissue Expression of Interferon Regulatory Factor (IRF)-5 in Obesity: Association with Metabolic Inflammation

Abstract: Interferon regulatory factor (IRF)-5 is known to be involved in M1 macrophage polarization, however, changes in the adipose expression of IRF5 in obesity and their relationship with the local expression of proinflammatory cytokines/chemokines are unknown. Therefore, IRF5 gene expression was determined in the subcutaneous adipose tissue samples from 53 non-diabetic individuals (6 lean, 18 overweight, and 29 obese), using real-time RT-PCR. IRF5 protein expression was also assessed using immunohistochemistry and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 65 publications
(72 reference statements)
3
27
0
1
Order By: Relevance
“…In 2008, Patsouris and colleagues demonstrated that the ablation of CD11c + cells during obesity restored insulin sensitivity by decreasing inflammatory markers (68). Interferon regulatory factor IRF5 is a pro-inflammatory transcription factor, commonly restricted to CD11c + cells, driving macrophage polarization toward an M1 phenotype (69), and is notably induced in ATMs in diet-induced obesity (70,71).…”
Section: Adipose Tissue Macrophages and Metabolic Inflammationmentioning
confidence: 99%
“…In 2008, Patsouris and colleagues demonstrated that the ablation of CD11c + cells during obesity restored insulin sensitivity by decreasing inflammatory markers (68). Interferon regulatory factor IRF5 is a pro-inflammatory transcription factor, commonly restricted to CD11c + cells, driving macrophage polarization toward an M1 phenotype (69), and is notably induced in ATMs in diet-induced obesity (70,71).…”
Section: Adipose Tissue Macrophages and Metabolic Inflammationmentioning
confidence: 99%
“…The signature inflammatory chemokines that are implicated with metabolic inflammation belong to the subfamilies CXC (e.g., 5,8,9), CC (e.g., CCL-2, 3,4,5,7,19), and CX3C (e.g., CX3CL-1). Notably, elevated levels of these chemokines in obesity/T2D have been linked to adipose tissue inflammation and insulin resistance [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…IRF5 orchestrates the macrophage polarization into inflammatory M1 phenotype and it positively modulates the adipose tissue deposition and insulin resistance in obesity [26]. We recently reported that increased adipose tissue IRF5 expression in non-diabetic obese individuals associated with BMI, Cells 2020, 9,730 3 of 20 percent body fat (PBF), and potential markers of adipose inflammation [20]; however, subcutaneous adipose tissue IRF5 expression in the diabetic obese patients and the relationship between IRF5 expression and signatures of metabolic inflammation still remain unclear. Herein, we present the data supporting that IRF5 expression in the subcutaneous adipose tissue associate with BMI, PBF, insulin, and homeostatic model assessment of insulin resistance (HOMA-IR) in diabetic lean/overweight patients while the adipose tissue IRF5 upregulation parallels with adipose inflammatory signatures in diabetic obese patients.…”
Section: Introductionmentioning
confidence: 99%
“…The women were healthy at the recruitment (in the 10-14th week). The mean age of the women in the LGA group was 36.0 years (range [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], and in the AGA group, it was 35.7 years (range 25-44) (p = 0.556). The differences between the groups were not statistically significant in terms of several risk factors of LGA and microelements' levels.…”
Section: Resultsmentioning
confidence: 97%
“…However, the associations between selenium levels and glucose metabolism and insulin resistance in humans are divergent; both lower and higher Se levels were associated with type 2 diabetes [1,34]. Recent evidence indicates that oxidative stress (reactive oxygen species (ROS) and stress of the endoplasmic reticulum) and inflammation in the hypothalamus affect its food intake-regulating functions and energy expenditure, and the major antioxidant enzymes in the brain include selenium-dependent GPx and ThRedx, as well as Cu, Zn-superoxide dismutase [40][41][42][43]. Selenium can also affect metabolic disorders through its association with thyroid hormone function [10,44].…”
Section: Discussionmentioning
confidence: 99%